Assessment of the potential of a high frequency acoustomicrofluidic nebulisation platform for inhaled stem cell therapy. Issue 1 (27th November 2015) - Alhasan, Layla; Qi, Aisha; Rezk, Amgad R.; Yeo, Leslie Y.; Chan, Peggy P. Y.
Abstract : This study demonstrates the use of a novel high frequency acoustic nebulisation platform as an effective aerosolisation technique for inhaled mesenchymal stem cell (MSC) therapy. Abstract : Despite the promise of stem cell therapy for lung therapeutics and repair, there are few viable means for directly delivering stem cells to locally target the respiratory airways via inhalation. This is not surprising given the significant challenges in aerosolising stem cells, particularly given their susceptibility to damage under the large stresses involved in the nebulisation process. Here, we present promising results using a microfluidic acoustic nebulisation platform that is not only low cost and portable, but also its high MHz order frequencies are effective for preserving the structural and functional integrity of mesenchymal stem cells (MSCs) during the nebulisation process. This is verified through an assessment of the viability, structure, metabolic activity, proliferation ability and genetic makeup of the nebulised MSCs using a variety of assays, including cell viability staining, flow cytometry, reverse transcription and quantitative polymerase chain reaction, and immunophenotyping, thus demonstrating the platform as a promising method for efficient pulmonary stem cell delivery.